Actor fluidity and knowledge persistence in regional inventor networks - Michael Fritsch; Moritz Zöllner (Friedrich Schiller University Jena, 2018)
The development of inventor networks is characterized by the addition of a significant number of new inventors, while a considerable number of incumbent inventors discontinue. We estimate the persistence of knowledge in regional inventor networks using alternative assumptions about knowledge transfer. Based on these estimates we analyze how the size and structure of a network may influence knowledge persistence over time. In a final step, we assess how persistent knowledge as well as the knowledge of new inventors effect the performance of regional innovation systems (RIS). The results suggest that the knowledge of new inventors is much more important for RIS performance than old knowledge that persists.
Keywords: O3; R1; D2; D8; 330; innovation networks; knowledge; RandD cooperation; patents; persistence